Covalent Attachment of Aggregation-Induced Emission Molecules to the Surface of Ultrasmall Gold Nanoparticles to Enhance Cell Penetration - Kai Klein; Matthias Hayduk; Sebastian Kollenda; Marco Schmiedtchen; Jens Voskuhl; Matthias Epple (Molecules, 2022)
Three different alkyne-terminated aggregation-induced emission molecules based on a para-substituted di-thioether were attached to the surface of ultrasmall gold nanoparticles (2 nm) by copper-catalyzed azide–alkyne cycloaddition (click chemistry). They showed a strong fluorescence and were well water-dispersible, in contrast to the dissolved AIE molecules. The AIE-loaded nanoparticles were not cytotoxic and easily penetrated the membrane of HeLa cells, paving the way for an intracellular application of AIE molecules, e.g., for imaging.